Serodiagnosis of aspergillosis in falcons (Falco spp.) by an Afmp1p‐based enzyme‐linked immunosorbent assay. Issue 8 (20th June 2018) - Wernery, Ulrich; Tsang, Chi‐Ching; Hebel, Christiana; Damerau, Alexandra; Kinne, Jörg; Cai, Jian‐Piao; Küspert, Harald; Chan, Ka‐Fai; Joseph, Marina; Xue, Shaolong; Raghavan, Rekha; Tang, James Y. M.; et al.
Summary: Aspergillosis in falcons may be associated with high mortality and difficulties in clinical and laboratory diagnosis. We previously cloned an immunogenic protein, Afmp1p, in Aspergillus fumigatus and showed that anti‐Afmp1p antibodies were present in human patients with A. fumigatus infections. In this study, we hypothesise that a similar Afmp1p‐based enzyme‐linked immunosorbent assay (ELISA) could be applied to serodiagnose falcon aspergillosis. A specific polyclonal antibody was first generated to detect falcon serum IgY. Horseradish peroxidase‐conjugate of this antibody was then used to measure anti‐Afmp1p antibodies in sera collected from falcons experimentally infected with A. fumigatus, and the performance of the Afmp1p‐based ELISA was evaluated using sera from healthy falcons and falcons with documented A. fumigatus infections. All four experimentally infected falcons developed culture‐ and histology‐proven invasive aspergillosis. Anti‐Afmp1p antibodies were detected in their sera. For the Afmp1p‐based ELISA, the mean ± SD OD450 nm using sera from 129 healthy falcons was 0.186 ± 0.073. Receiver operating characteristics curve analysis showed an absorbance cut‐off value of 0.407. One negative serum gave an absorbance outside the normal range, giving a specificity of 99.2%. For the 12 sera from falcons with confirmed aspergillosis, nine gave absorbance values ≥ cut‐off, giving a sensitivity of 75%. The Afmp1p‐based ELISA is useful for serodiagnosis of falcons with aspergillosis.